3‐Bromopyruvate as a potent anticancer therapy in honor and memory of the late Professor André Goffeau. Issue 4 (13th December 2018) - Ko, Young H.; Niedźwiecka, Katarzyna; Casal, Margarida; Pedersen, Peter L.; Ułaszewski, Stanisław
Abstract: 3‐Bromopyruvate (3BP ) is a small, highly reactive molecule formed by bromination of pyruvate. In the year 2000, the antitumor properties of 3BP were discovered. Studies using animal models proved its high efficacy for anticancer therapy with no apparent side effects. This was also found to be the case in a limited number of cancer patients treated with 3BP . Due to the "Warburg effect, " most tumor cells exhibit metabolic changes, for example, increased glucose consumption and lactic acid production resulting from mitochondrial‐bound overexpressed hexokinase 2. Such alterations promote cell migration, immortality via inhibition of apoptosis, and less dependence on the availability of oxygen. Significantly, these attributes also make cancer cells more sensitive to agents, such as 3BP that inhibits energy production pathways without harming normal cells. This selectivity of 3BP is mainly due to overexpressed monocarboxylate transporters in cancer cells. Furthermore, 3BP is not a substrate for any pumps belonging to the ATP‐binding cassette superfamily, which confers resistance to a variety of drugs. Also, 3BP has the capacity to induce multiple forms of cell death, by, for example, ATP depletion resulting from inactivation of both glycolytic and mitochondrial energy production pathways. In addition to its anticancer property, 3BP also exhibits antimicrobial activity. Various species of microorganisms are characterized by different susceptibility to 3BP inhibition. Among tested strains, the most sensitive was found to be the pathogenic yeast‐like fungus Cryptococcus neoformans . Significantly, studies carried out in our laboratories have shown that 3BP exhibits a remarkable capacity to eradicate cancer cells, fungi, and algae.